Utilization of steelmaking by-products in the construction industry: A comprehensive review of steel slag and steel mill scale - Nancy Soliman; Hossein Roghani; Iman Aghayan; Ahmed Omran; Konstantin Sobolev (Case Studies in Construction Materials)
The rapid urbanization projected by 2050 necessitates sustainable infrastructure development to accommodate the growing population. Concrete, the primary material for construction, significantly contributes to global CO2 emissions, accounting for 6–8 % of global emissions. This underscores the urgent need for innovative solutions in the cement and concrete industry. Steelmaking by-products, particularly steel slag and steel mill scale (SMS), offer promising avenues for enhancing the sustainability and performance of concrete. This review evaluates the type, chemical and physical properties of steel slag and SMS, their mechanical and durability impacts on concrete, and the environmental benefits of their utilization. Additionally, it comprehensively explores the potential applications of steel slag and SMS in the construction sector, focusing on their roles as aggregates, supplementary cementitious materials (SCMs), and their capability for CO2 capture and sequestration. The paper also addresses the global utilization of these by-products and their applications in transportation infrastructure. Key challenges, including volume instability due to free lime and magnesium oxide, variability in composition, and heavy metal leaching, are discussed alongside potential solutions such as pre-treatment and blending with other SCMs. Future opportunities are highlighted, emphasizing the need for standardized guidelines, large-scale field applications, and economic and life cycle assessments to facilitate broader adoption. By addressing these gaps, steel slag and SMS can significantly contribute to sustainable construction practices, reducing environmental impacts and enhancing resource efficiency.